The job guarantee: MMT's proposal for full employment and price stability - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2024)
Orthodox economic theory presents the policy maker with an impossible choice: eradicate unemployment at the cost of undesirable inflation or keep prices stable by maintaining some level of involuntary unemployment. This is the canon, as embodied in the natural rate of unemployment theory and the Non-Accelerating Inflation Rate of Unemployment (NAIRU). In the mainstream, there is no alternative. Heterodoxy has long criticized the NAIRU and the natural rate, but has not mounted a robust challenge for lack of a clearly articulated policy alternative that can target both goals: full employment and price stability. Modern Money Theory (MMT) has such a proposal-the federal Job Guarantee.
Keywords: 330; Full employment; Full employment policy; Job guarantee; Modern Money Theory (MMT)